2005
DOI: 10.1124/dmd.105.005280
|View full text |Cite
|
Sign up to set email alerts
|

INHIBITION OF LUNG CANCER CELL GROWTH BY QUERCETIN GLUCURONIDES VIA G2/M ARREST AND INDUCTION OF APOPTOSIS

Abstract: ABSTRACT:Lung cancer is the leading cause of cancer death in many developed countries, including Taiwan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 49 publications
(54 reference statements)
4
120
1
2
Order By: Relevance
“…Additionally, CHC has also been identified as an inhibitor of the anion exchanger 1 (Deuticke 1982), an important pH regulator that is responsible for Cl K /HCO 3 K membrane exchange (Kopito 1990). Different effects have been identified as mediating the antitumour activity of quercetin, including cell cycle arrest (Yang et al 2006) and apoptosis (Granado-Serrano et al 2006, Yang et al 2006, as well as inhibition of the phosphatidylinositol 3-kinase/Akt pathway Granado-Serrano et al 2006). However, we observed that quercetin only affected the MCT1-positive breast cancer cells at the metabolic level with no disturbance in the metabolic behaviour of MCT1-negative breast cancer cell lines, indicating some preference for MCT inhibition.…”
Section: Discussioncontrasting
confidence: 40%
“…Additionally, CHC has also been identified as an inhibitor of the anion exchanger 1 (Deuticke 1982), an important pH regulator that is responsible for Cl K /HCO 3 K membrane exchange (Kopito 1990). Different effects have been identified as mediating the antitumour activity of quercetin, including cell cycle arrest (Yang et al 2006) and apoptosis (Granado-Serrano et al 2006, Yang et al 2006, as well as inhibition of the phosphatidylinositol 3-kinase/Akt pathway Granado-Serrano et al 2006). However, we observed that quercetin only affected the MCT1-positive breast cancer cells at the metabolic level with no disturbance in the metabolic behaviour of MCT1-negative breast cancer cell lines, indicating some preference for MCT inhibition.…”
Section: Discussioncontrasting
confidence: 40%
“…The flavone-induced G 2 -M arrest apparent in breast cancer cells in the present study was likely mediated by p21 Waf1 , which induces such arrest in a variety of cell types [33,34,35,36]. In contrast to its effects in malignant cells, flavone induced G 0 -G 1 arrest without apoptosis in nonmalignant breast epithelial cells, suggesting that nonmalignant cells might be able to regain their proliferative capacity.…”
Section: Discussionmentioning
confidence: 44%
“…Survivin, a member of the inhibitor of apoptosis gene family, is expressed in a cell cycle-dependent manner, increasing in the G2/M phase of the cell cycle followed by a rapid decline in the G1 phase [26,27]. Recent studies have revealed that quercetin inhibits cell proliferation by causing cell cycle arrest in G2/M phase [28,29]. Although quercetin causes cells to arrest in G2/M phase, expression of survivin is down-regulated by treatment with quercetin (Fig.…”
Section: Discussionmentioning
confidence: 99%